Breastfeeding, feeding practices and stunting in indigenous Ecuadorians under 2 years of age - Betzabé Tello; María F. Rivadeneira; Ana L. Moncayo; Janett Buitrón; Fabricio Astudillo; Andrea Estrella; Ana L. Torres (BMC, 2022)
Abstract Background The indigenous child population in Ecuador has a high prevalence of stunting. There is limited evidence of the association between breastfeeding, feeding practices, and stunting in indigenous children. This study aimed to analyze the prevalence of breastfeeding and complementary feeding practices and explore their association with stunting in Ecuadorian indigenous children under two years of age. Methods Cross-sectional study of secondary data analysis using the 2012 Ecuador National Health and Nutrition Study, in 625 children aged 0-23 months (48,069 expanded sample), representative for the indigenous population. Breastfeeding and complementary feeding indicators were analyzed by age groups. Timely initiation of breastfeeding (within one hour after birth), exclusive breastfeeding (infants under six months who received only breast milk for the previous day), and other indicators were measured. Chi-square test or Fisher's exact test and logistic regression for complex samples were used to explore association with demographic and socioeconomic factors and stunting. Results Twenty-six-point eight percent of the children were stunted. Stunting occurred mainly in children with rural residence, on poor households, and where there were four or more children. Most of the children had a timely initiation of breastfeeding (69.5% for 0-12 months and 75.5% for 13-23 months) and exclusive breastfeeding up to six months (78.2%). Among children between 6-12 months of age, 99.3% continued to be breastfed. In children from ages 6 to 12 months, 32.5% received food with adequate dietary diversity. Lower percentages of complementary feeding occurred in the poorest, adolescent mothers or those with less education. Children who did not receive the minimum frequency of meals for their age had higher odds of stunting (OR 3.28; 95% CI 1.3, 8.27). Children from age 19 to 23 months who consumed foods rich in iron showed lower probabilities of stunting (OR 0.04; 95% CI 0.00, 0.51). Conclusions Breastfeeding practices reached a prevalence of 70% or more, without being associated with stunting. Complementary feeding practices showed differences by socioeconomic condition. Not reaching the minimum meal frequency between 6 and 12 months of age was associated with stunting. Plans and strategies are necessary to promote adequate feeding and breastfeeding practices in the indigenous population.